2019
DOI: 10.1186/s12889-019-7619-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal variation and risk factor analysis of hand, foot, and mouth disease in children under 5 years old in Guangxi, China

Abstract: BackgroundHand, foot and mouth disease (HFMD) incidence is a critical challenge to disease control and prevention in parts of China, particularly Guangxi. However, the association between socioeconomic factors and meteorological factors on HFMD is still unclear.MethodsThis study applied global and local Moran’s I to examine the spatial pattern of HFMD and series analysis to explore the temporal pattern. The effects of meteorological factors and socioeconomic factors on HFMD incidence in Guangxi, China were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In our study, the DCC size, based on the number of children, was a significant factor associated with HFMD in northern Thailand, and this result coincides with a study conducted in China reporting that children living in high-density areas had a greater chance of HFMD infection than those living in low-density areas [28]. Two more studies in China clearly demonstrated the association between population density and the occurrence of HFMD [29,30]. However, a study in Bangkok, Thailand reported that the most important factor underlying HFMD outbreaks was the number of close contacts with infected people [31], while density was not found to be associated with HFMD.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the DCC size, based on the number of children, was a significant factor associated with HFMD in northern Thailand, and this result coincides with a study conducted in China reporting that children living in high-density areas had a greater chance of HFMD infection than those living in low-density areas [28]. Two more studies in China clearly demonstrated the association between population density and the occurrence of HFMD [29,30]. However, a study in Bangkok, Thailand reported that the most important factor underlying HFMD outbreaks was the number of close contacts with infected people [31], while density was not found to be associated with HFMD.…”
Section: Discussionsupporting
confidence: 90%
“…To sum up, most of previous studies were mostly concentrated in areas with high incidence of HFMD, such as Hongkong [ 20 ], Guangdong [ 13 ], Guangxi [ 23 ] and Jiangsu [ 24 ]. The climate in these areas is significantly different from that in arid and semi-arid areas in Northwest China.…”
Section: Introductionmentioning
confidence: 99%
“…It analyzes the effects of atmospheric pollution and climatic factors on such incidences in northwestern China simultaneously for the very time, offering important implications for reducing them in western China, as well as for other regions with similar natural and social environments, such as the central region of the United States and Afghanistan. Besides meteorological factors and atmospheric pollutants, experts such as Gao et al ( 21 ), Liu et al ( 22 ), and Sun et al ( 23 ) have also started to gradually focus on the influence of socioeconomic factors on HFMD in recent years, providing ideas for further development of our study.…”
Section: Introductionmentioning
confidence: 99%